Maintaining the Quality and Storage Life of Strawberries (Fragaria × ananassa Duch.) with Melatonin and Methyl Jasmonate - Sercan DÜZGÜN; Şeyda ÇAVUŞOĞLU (ISPEC Journal of Agricultural Sciences)
In this study, the effects of post-harvest applications of melatonin and methyl jasmonate (MeJA) on the quality parameters of Albion strawberries during the storage process were examined. The results showed a continuous increase in pH values during storage; The highest value was recorded in the 1 µmol L-1 MeJA group and the lowest value was observed in the 0.5 mMol L-1 Melatonin group. TSS content decreased in all treatments during storage due to increased respiration. Similarly, titratable acidity initially increased but decreased at the end of storage. In particular, it has been observed that administration of 0.5 mMol L-1 melatonin slows down the decrease in titratable acidity. There were fluctuations in color parameters (L*, a*, b*, C*, h°) during storage, and both melatonin and MeJA applications were effective in maintaining the L* value. MeJA application showed superior results in preserving overall color values. Respiratory rate increased initially and decreased after storage day 12; both melatonin and MeJA administrations contributed to the reduction in respiratory rate. The tanning index fluctuated across all treatments; Melatonin-treated groups showed the highest index at the end of storage. MeJA applications were more effective in protecting pH, TSS, L* value and color tone value. In conclusion, it can be said that post-harvest treatments of melatonin and MeJA have significant effects on quality parameters during the storage process of Albion strawberries and contribute to the understanding of post-harvest management strategies to increase the shelf life and quality of strawberry fruits